Short and long term prognosis of acute myocardial infarction since introduction of thrombolysis. Issue 6900 (7th August 1993) - Stevenson, R; Ranjadayalan, K; Wilkinson, P; Roberts, R; Timmis, A D
Abstract : OBJECTIVE--To record prognosis and determinants of outcome in patients with acute myocardial infarction since thrombolysis was introduced. DESIGN--Observational study. SETTING--London district general hospital. PATIENTS--608 consecutive patients admitted to the coronary care unit with acute myocardial infarction between 1 January 1988 and 31 December 1991. MAIN OUTCOME MEASURE--All cause mortality, non-fatal ischaemic events (myocardial infarction, unstable angina), and revascularisation. RESULTS--Of the 608 patients, 89 (14.6%) died in hospital. 507 [corrected] patients were followed up after discharge from hospital. Mortality (95% confidence interval) at 30 days, one year, and three years was 16.0% (13.4% to 19.2%), 21.7% (18.6% to 25.2%), and 29.4% (25.3% to 33.9%) respectively. Event free survival (survival without a non-fatal ischaemic event) was 80.4% (77.0% to 83.4%) at 30 days, 66.8% (62.8% to 70.5%) at one year, and 56.1% (51.3% to 60.6%) at three years. Survival in patients treated with thrombolysis was considerably higher than in those not given thrombolysis (three year survival: 76.7% v 54.3%), although the incidence of non-fatal ischaemic events was the same in the two groups. Multivariate determinants of six month survival were left ventricular failure, treatment with thrombolysis and aspirin, smoking history, bundle branch block, and age. For patients who survived six months, age was the only factor related to long term survival. CONCLUSIONS--Although patients treated by thrombolysis had a relatively good prognosis, long term mortality and the incidence of non-fatal recurrent ischaemic events remained high. Effective strategies for the identification and treatment of high risk patients need to be reassessed.